Review and new insights into wood anatomy that help understand and control oak wilt - Rioux, Danny; Blais, Martine (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2023)
Oak wilt, which develops in the outer sapwood, is the most destructive disease of oaks in the United States. Species of red oaks are more susceptible to this disease than white oak species and are more likely to facilitate the spread of the pathogen Bretziella fagacearum. To prevent its establishment in new areas, phytosanitary certificates are mandatory for commercial trade, as is the inspection of logs to confirm identification. A literature survey and the results of our assays with seven oak species confirm that it is easy to identify wood of the red and white oak groups using anatomical features. Specifically, earlywood vessels are generally open in red oaks, while they appear occluded with tyloses in white oaks. Such plugs are the consequence of air embolism (cavitation) and not the cause of the wilting process. Although these wide vessels are efficient for water transport, they are vulnerable to cavitation that appears to favour the growth of the oak wilt pathogen. Compartmentalization of infected wood succeeds in restraining cavitation and pathogen spread, allowing some trees to recover from oak wilt.